Analisis Yuridis Tentang “Agile Working” dari Sudut Pandang Hukum Ketenagakerjaan Positif di Indonesia - Joshua Evandeo Irawan; Dwi Foni Yunita Nur Asyah (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2023)
The Covid-19 pandemic has resulted in the adoption of flexible work systems called Agile Working, which combines work flexibility and technology. This research focused on Indonesian labor laws, namely UU 13/2003, Law No. 6 of 2023, and PP No. 35/2021, to establish legal certainty for Agile Working. Previous research identified a lack of legal framework for remote working, which shares similarities with Agile Working. This research aimed to address this gap by providing new insights and findings. Using the Dogmatic Normative Juridical Method, the researchers analyzed Agile Working within the framework of Indonesian labor law. The researchers engaged in a literature review, encompassing laws, regulations, court decisions, and other legal literature, to thoroughly examine the relevant legal provisions. This involved assessing compliance with labor regulations such as the Manpower Law, government regulations, and labor policies. Relevant court decisions were also considered for legal interpretation.The research concluded that Agile Working could be implemented in Indonesia with legal protection, particularly concerning Working Time and Overtime Pay. The authors recommended that workers and employers adhering to Agile Working in Industrial Relations must uphold their rights and obligations to ensure compliance with the law. To summarize, this research updated previous studies on Agile Working, offering fresh insights and contributions. Through the normative research method, the authors analyzed and interpreted labor laws, providing a deeper understanding of how Agile Working aligns with Indonesian labor law. The research confirmed the legal implementation of Agile Working in Indonesia, emphasizing the importance of respecting rights and obligations.